The scapegoat theory of exchange rates: the first tests - Marcel Fratzscher; Lucio Sarno; Gabriele Zinna (European Central Bank (ECB), 2012)
This paper provides an empirical test of the scapegoat theory of exchange rates (Bacchetta and van Wincoop 2004, 2011), as an attempt to evaluate its potential for explaining the poor empirical performance of traditional exchange rate models. This theory suggests that market participants may at times attach significantly more weight to individual economic fundamentals to rationalize the pricing of currencies, which are partly driven by unobservable shocks. Using novel survey data which directly measure foreign exchange scapegoats for 12 currencies and a decade of proprietary data on order flow, we find empirical evidence that strongly supports the empirical implications of the scapegoat theory of exchange rates, with the resulting models explaining a large fraction of the variation and directional changes in exchange rates. The findings have implications for exchange rate modelling, suggesting that a more accurate understanding of exchange rates requires taking into account the role of scapegoat factors and their time-varying nature.
Keywords: F31; G10; 330; economic fundamentals; Exchange Rates; order flow; Scapegoat; survey data